The Influence Of Economic Value Added (EVA), Return On Assets (ROA) On Stock Prices With Market Value Added (MVA) As A Moderating Variable - Retno Ulfayatun Hidayah; Ade Famalika; Arisky Andrinaldo; Yuli Nurhayati; Nur Uswatun Hasana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research is to ascertain the influence of Economic Value Added (EVA), Return on Assets (ROA) on stock prices with Market Value Added (MVA) as a moderating variable in retail sector companies on the Indonesian Stock Exchange for the 2017-2022 period. The research methodology used is a quantitative method. The research population and sample consisted of 30 data. In this research, the data collection techniques used in this research were documentation and library research techniques. Data were analyzed using panel data regression, Microsoft Excel 2010 and Eviews Version 12 were used to process the data. Findings: The results of the t test (partial) on the Economic Value Added (EVA) variable (X1) obtained a calculated t value of 0.434167 < t table, namely 2.048407142 and a sig value. 0.6676 > 0.05, then H1 is rejected. The results of the t test (partial) on the Return on Assets (ROA) variable obtained a calculated t value of 12.77570 > t table, namely 2.048407142 and a sig value. 0.0000 < 0.05, then H2 is accepted. The results of the t test (partial) on the moderating variable Market Value Added (MVA) are able to moderate Economic Value Added (EVA) and obtain a sig level value. is 1.288399 > 0.05 and the sig.prob value is 0.2094 < 0.05, then H3 is accepted. The results of the t test (partial) on the Market Value Added (MVA) moderating variable are able to moderate the Return on Assets (ROA) to obtain a sig level value. is -0.916624 < 0.05 and the sig.prob value is 0.3681 > 0.05, then H4 is rejected.